2004
DOI: 10.1007/s00330-003-2045-y
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck lesions in the immunocompromised host

Abstract: Head and neck lesions are encountered in more than 40-50% in patients with immunosuppression (HIV-infected individuals, diabetes mellitus, transplant recipients, patients treated with immunosuppressive drugs or post-radiotherapy). The organs affected are the salivary glands, the lymph nodes, the sinonasal tract, the orbits, the temporal bones, and the pharyngo-laryngeal mucosa. They are mainly involved by granulation tissue, perivascular and perineural inflammation, and neoplasms. In the pediatric population t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 10 publications
1
21
0
3
Order By: Relevance
“…They reported Kaposi's sarcoma and NHL as the most common lesions, with frequencies of occurrence of 20 000 and 60Á70, respectively, compared with the general population. High rates of salivary gland diseases, not necessarily tumours, were observed by Marsot-Dupuch et al [15], Imogu [16], Nwaorgu et al [17] and Bakari et al [18]. Marsot-Dupuch et al attributed this to a probable increase in HIV concentration in saliva.…”
Section: Discussionmentioning
confidence: 69%
“…They reported Kaposi's sarcoma and NHL as the most common lesions, with frequencies of occurrence of 20 000 and 60Á70, respectively, compared with the general population. High rates of salivary gland diseases, not necessarily tumours, were observed by Marsot-Dupuch et al [15], Imogu [16], Nwaorgu et al [17] and Bakari et al [18]. Marsot-Dupuch et al attributed this to a probable increase in HIV concentration in saliva.…”
Section: Discussionmentioning
confidence: 69%
“…Giunta and Cataldo 13) and Buchner and Hansen 7) also observed that these cysts may vary in diameter from 2 to 15 mm. OLCs occurring on the parotid gland are often associated with immunocompromised patients and lymphoproliferative disorders 20) . Table 1 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Diseases involving the head and neck area are often the first signs of an immune compromised body and may occur in as many as 40% to 90% of individuals with HIV/AIDS [5][6][7][8][9]. Common HIV/AIDSassociated head and neck pathologies include manifestations in the central nervous system (CNS), the naso-, oro-and laryngopharynx and in the inner ear, that may result in hearing loss and/or vestibular disorders [10][11][12].…”
Section: Introductionmentioning
confidence: 99%